Selenium and thyroid diseases - Wang, Fei; Li, Chunyu; Li, Shaoxin; Cui, Lili; Zhao, Junyu; Liao, Lin (Frontiers in Endocrinology, 2023)
Selenium, a non-metallic element, is a micronutrient essential for the biosynthesis of selenoproteins containing selenocysteine. In adults, the thyroid contains the highest amount of selenium per gram of tissue. Most known selenoproteins, such as glutathione peroxidase, are expressed in the thyroid and are involved in thyroid hormone metabolism, redox state regulation, and maintenance of cellular homeostasis. Some clinical studies have shown that lack of selenium will increase the prevalence of several kinds of thyroid diseases. Selenium treatment in patients with Graves' orbitopathy has been shown to delay disease progression and improve the quality of life. Selenium supplementation in Hashimoto's thyroiditis was associated with the decreased levels of anti-thyroid peroxidase antibody and improved thyroid ultrasound structure. In thyroid cancer, various selenium supplements have shown variable anticancer activity. However, published results remain the conflicting and more clinical evidence is still needed to determine the clinical significance of selenium. This article reviews the strong association between selenium and thyroid disease and provides new ideas for the clinical management of selenium in thyroid disease.